Sementes de feijão-caupi (Vigna unguiculata L. (Walp), tratadas com extrato de folhas de nim (Azadirachta indica A. Juss.) avaliação da germinação e da incidência de fungos - Silva, Gilvânia Campos [UNESP] (2011)
This study aimed to evaluate the effect of aqueous extract of neem on germination and fungi incidence on seeds of three cultivars (Serrinha, BR 17 and Maranhão) of cowpea. Neem leaves were dryed, crushed and prepared dilutions of 0.5; 1.0; 2.0, 4.0 g dm -3and control. The fungi incidence was evaluated by the test filter paper and germination according to the Rules for Seeds Testing (Regras para Análise de Sementes). In the three cultivars analyzed, reduction in the incidence of Aspergillus sp and Fusarium sp was observed. In relation to the influence of extracts of neem leaves on seed germination, significant effect of extract in Maranhão cultivar was observed, where all concentrations differed from the control, and propovided a considerable increase in the percentage of normal seedlings. It was concluded that the leaf extract of neem was effective in controlling Aspergillus sp, Fusarium sp , Phoma sp and Macrophomina phaseolina at different concentrations in different cultivars and seed germination was stimulated for the Maranhão cultivar.